Business Model and Competitive Strategy Development for a Private Hospital Under National Health Insurance Expansion - Christian Prijana; Mohammad Riza Sutjipto (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
The rapid expansion of Indonesia's National Health Insurance (JKN) program has transformed the healthcare sector, creating strategic challenges for secondary-level private hospitals in semi-rural areas. Following cooperation with BPJS Kesehatan in July 2025, RS Mitra Plumbon Patrol experienced a substantial increase in patient volume, with bed occupancy rates rising from 63.83% to 99.63% within four months. This growth exposed a misalignment between the hospital's existing business model and its evolving internal and external environment, requiring business model innovation to maintain competitive advantage and financial sustainability. This study aimed to analyze the existing business model, identify internal and external competitiveness factors, and formulate a recommended business model to strengthen organizational performance. A qualitative single embedded case study was conducted using an interpretivist approach. Data were collected through in-depth interviews with ten purposively selected informants and validated through source triangulation. Data analysis integrated the Business Model Canvas, PESTEL analysis, Porter's Five Forces, and SWOT matrix. The findings revealed that approximately 80–90% of patients were covered by BPJS. Key strengths included a trauma center, five-star accreditation, and organizational support, whereas weaknesses included BPJS revenue dependence, high employee turnover, and limited referral access. Four strategic priorities were identified: premium medical check-up services, business-to-business marketing expansion, strengthened BPJS claim documentation, and staff retention with patient loyalty programs. The proposed business model targets a 60% BPJS and 40% non-BPJS patient composition through diversified revenue streams, providing a replicable framework for improving competitiveness, financial resilience, operational efficiency, and sustainable healthcare service quality in resource-constrained private hospitals undergoing insurance-driven transformation.